1980
DOI: 10.1007/bf00381521
|View full text |Cite
|
Sign up to set email alerts
|

Results of endoprosthetic hip joint replacement with the aluminum ceramic-metal composite prosthesis “lindenhof”

Abstract: The first clinical results of the Lindenhof ceramic-metal composite prosthesis implanted in our hospital in Freiburg are presented. We observed that same favorable early results as the conventional prostheses in a correct position. The implants are incorporated into the bone within 8-12 weeks. The radiographic films show the adaptation of the supporting bone around the ceramic socket. We explain the failures due to our initial lack of technical experience and/or anatomical deformation of the pelvic bone. compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Many investigations have shown predominantly good clinical results [8][9][10][11][12][13][14]. Some authors, however, reported a higher rate of ceramic components from postheses retrieved at revision surgery [15]; excessive wear is initiated when ceramic grains are torn from the high-gloss polished articular surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have shown predominantly good clinical results [8][9][10][11][12][13][14]. Some authors, however, reported a higher rate of ceramic components from postheses retrieved at revision surgery [15]; excessive wear is initiated when ceramic grains are torn from the high-gloss polished articular surfaces.…”
Section: Discussionmentioning
confidence: 99%